FRAUND DIAMOND DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Poppy Indriani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
Effect of Diamond Fraud in Financial Statement Fraud detection. This study aimed to get empirical evidence regarding the effectiveness of diamond fraud in detecting fraudulent financial statements. Variables - variables of diamond fraud is financial stability is proxied by ACHANGE, external pressure proxied with leverage, financial targets are proxied by the ROA, nature of industry proxied by inventory, ineffective monitoring proxied by BDOUT, audit opinion and change of directors. Financial statement fraud detection in this study using the F-score models. The results of this study indicate that external pressure, financial targets, ineffective monitoring, audit opinion and change of directors does not have influence in detecting fraudulent financial statements. While the financial stability and nature of industry to have an influence in detecting fraudulent financial statements.